Comparison of image quality and radiation dose between an image-intensifier system and a newer-generation flat-panel detector system: technical phantom measurements and evaluation of clinical imaging in children - Weis, Meike; Henzler, Claudia; Schönberg, Stefan; Neff, Wolfgang (Pediatric radiology, 2016)
Background: Many image-intensifier fluoroscopy systems have been replaced by flat-panel detectors in recent years. Objective: To compare the level of contrast, image resolution and radiation dose between an image-intensifier and a newer-generation flat-panel detector system in a pediatric radiology unit. Materials and methods: We compared two systems - a conventional image intensifier and a newer-generation flat-panel system. We measured image quality and radiation dose using a technical phantom. Additionally, we retrospectively compared age-matched fluoroscopic pediatric voiding cystourethrography (n = 15) and upper gastrointestinal investigations (n = 25). Results: In phantom studies image contrast was equal while image resolution was higher and mean radiation dose lower using the flat-panel system (P < 0.0001). In pediatric investigations, mean dose area product was significantly reduced on the flat-panel system for upper gastrointestinal investigation (45 ± 38 μGy*m2 vs. 11 ± 9 μGy*m2; P < 0.0001) and for voiding cystourethrography (18 ± 20 μGy*m2 vs. 10 ± 12 μGy*m2; P = 0.04). Conclusion: The newer flat-panel system performs at lower dose levels with equal to better image quality and therefore seems to be the more suitable technique for pediatric fluoroscopy in comparison to image-intensifier systems.